STRATEGI GURU DALAM MENINGKATKAN KEMAMPUAN MEMBACA PERMULAAN SISWA KELAS 1 SEKOLAH KITA CIBANOANG - Putri Sholehah, Rizki; Iswandi, Irvan; Utami, Dewi (Sindoro: Cendikia Pendidikan, 2024)
Reading is a way to explore information and knowledge from written texts in order to gain extensive knowledge and new experiences. Success in learning to read at school has an influence on literacy development and students' overall learning abilities. Therefore, teachers need to apply appropriate strategies to attract students' interest so that they are more enthusiastic in the process of learning to read. This research aims to find out these strategies and find out the supporting and inhibiting factors for teacher strategies in improving the beginning reading skills of grade 1 students. This research uses a qualitative, descriptive approach. The research sample consisted of 1 teacher and 13 students selected by purposive sampling. Researchers act as key instruments with data collection techniques through observation, interviews, documentation and tests, then analyzed by data reduction, data presentation and drawing conclusions. The research results show that: 1) The strategies applied by teachers to improve beginning reading skills include: bottom-up, top-down and reading aloud strategies. It can be concluded that the initial reading strategies implemented by grade 1 teachers are quite varied and effective in improving the initial reading abilities of grade 1 students at Kita Cibanoang School. 2) Supporting factors for teacher strategies in improving initial reading skills, namely, infrastructure, parental support and school policies. Meanwhile, the inhibiting factor for teachers' strategies in improving initial reading skills is that there is no special scheduling for reading outside of effective learning hours. Keywords: strategy, teacher, beginning reading